Respuesta :

4c + 9 = [8c + 1 - (2c - 11)] / 3

4c + 9 = [8c + 1 - 2c + 11] / 3

4c + 9 = [6c + 12] / 3

4c + 9 = 2c + 4

2c + 9 = 4

2c = -5

c = -2/5

Hope this helps! ;)

The value of c is -5 / 2.

We are given,

4c + 9 = [ 8c + 1 - (2c - 11) ] / 3

We have to solve for c.

While solving this equation we need to be careful about the signs and use the operation carefully.

Let us solve for c.

4c + 9 = [ 8c + 1 - (2c - 11) ] / 3

Removing the brackets.

4c + 9 = ( 8c + 1 - 2c + 11 ) / 3

Removing the fraction.

3 x (4c + 9) = 6c + 12

Applying Distributive multiplication over addition.

12c + 27 = 6c + 12

Keeping the like terms in one place.

12c - 6c = 12 - 27

Making into a simpler form.

6c =  - 15

Dividing with 3.

c = -15 / 6

We get,

c = -5 / 2

Thus the value of c is -5 / 2.

Learn more about solving Unkown value here:

https://brainly.com/question/16981633

#SPJ2